Botany. Part B [electronic resource] : marine algae. - Collins, Frank Shipley, 1848-1920.; Canadian Arctic Expedition (1913-1918) (Ottawa : F.A. Acland, 1927)
Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 4, pt. B. Includes list of titles in the series. "Southern Party, 1913-16." Electronic reproduction. Mode of access: Internet. 44